2023
DOI: 10.1002/jemt.24323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interfacial adaptation and penetration of bioceramic‐based sealers in oval root canals: A confocal laser scanning microscope study

Abstract: To assess the interfacial adaptation and penetration depth of three different bioceramic‐based sealers (CeraSeal, EndoSeal MTA, Nishika Canal Sealer BG) compared to an epoxy resin‐based sealer (AH Plus) in oval root canals. Fourty extracted single‐rooted mandibular premolar with oval canal were prepared and randomly allocated according to the obturation into; CeraSeal, EndoSeal MTA, Nishika Canal Sealer BG and AH Plus. The roots were sectioned at 3, 6 and 9 mm from the apex. The sealer adaptation and the penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“… 22 , 23 Therefore, the small particle size and greater fluidity of the C 3 S-BG-P and Nishika allowed their better adaptation to root canal walls. Chew et al 30 compared three different sealers (EndoSeal MTA, CeraSeal, and Nishika Canal Sealer BG) with an AH Plus in oval root canals. Through the evaluation of the interfacial adaptability and depth of penetration at 3, 6, and 9 mm root sections from the apex under a confocal laser scanning microscope, they concluded that Nishika resulted in superior penetration and adaptation than the other tested sealers due to its superior physicochemical properties and fine particle size.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Therefore, the small particle size and greater fluidity of the C 3 S-BG-P and Nishika allowed their better adaptation to root canal walls. Chew et al 30 compared three different sealers (EndoSeal MTA, CeraSeal, and Nishika Canal Sealer BG) with an AH Plus in oval root canals. Through the evaluation of the interfacial adaptability and depth of penetration at 3, 6, and 9 mm root sections from the apex under a confocal laser scanning microscope, they concluded that Nishika resulted in superior penetration and adaptation than the other tested sealers due to its superior physicochemical properties and fine particle size.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation to the canal wall and penetration depth of the sealers CeraSeal, EndoSeal MTA, Nishika Canal Sealer BG and AH Plus have been studied [ 94 ]. Three levels, apical (3 mm from apex), middle (6 mm from the apex) and coronal (9 mm from the apex) were measured.…”
Section: Sealers and Cements Used In Endodontic Practicementioning
confidence: 99%
“…For the penetration depth, there were significant differences only at the coronal level. Nishika Canal Sealer BG had higher penetration depth than AH Plus and EndoSeal MTA, whereas CeraSeal showed higher penetration depths than EndoSeal MTA [ 94 ].…”
Section: Sealers and Cements Used In Endodontic Practicementioning
confidence: 99%